O núcleo de apoio à saúde da família (NASF) como mobilizador da práxis psicossocial - Moura, Renata Heller de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
For over three decades the brazilian psychiatric reform in line with health reform, is allowing us to see that the struggle for deinstitutionalization “insanity” is done not only by the “overthrow of the walls” of the psychiatric hospital, but also the struggle for “tear down the walls” of institutionalization that submits to all of us. The creation of extra-hospital devices is a major breakthrough in this process. However, alone, these devices do not guarantee the deconstruction of fragmented medicalizadoras and ineffective interventions. More than the creation of devices and programs, we need a networking developed from primary care by many devices for health care, mobilized by psychosocial practice. This research presents the Family Health Support Center (FHSC) as a resonance of the intertwining of reform movements in the health field in Brazil (health and psychiatric reforms). The FHSC is a program of the Ministry of Health, established in 2008, aiming to strengthen and broaden the scope of action of the Family Health Strategy, thus helping to catalyze the reorientation of the health care model in this country. Our interest was to investigate it as a device capable of mobilizing psychosocial practice and contribute to the development of mental health care within Primary Care. To this end, we seek to meet the proposals and actions taken by a professional FHSC in an inland city of Paraná. The research lies in the field of qualitative methodologies and has its methodological orientation guided by the concept of man as a historic, able to transform reality and be transformed by it, in a constant interaction with the social environment and the material world to be. From this methodological orientation, we use the concept of “praxis”, understanding it as a substantive activity of the human being who acts in history, causing changes that outweigh the social settings and trying to break through the repetitive practice to ...

Há mais de três décadas a Reforma Psiquiátrica brasileira, em consonância com a Reforma Sanitária, vem nos permitindo constatar que a luta pela desinstitucionalização da “loucura” não se faz somente pela “derrubada dos muros” do hospital psiquiátrico, mas também pela luta por “derrubar os muros” da institucionalização que submete a todos nós. A criação de dispositivos extra-hospitalares é um grande avanço nesse processo. No entanto, por si só, estes dispositivos não garantem a desconstrução de intervenções fragmentadas, medicalizadoras e ineficientes. Mais do que a criação de dispositivos e programas, precisamos de um trabalho em rede, desenvolvido desde a Atenção Básica pelos diversos dispositivos de atenção à saúde, mobilizados por uma práxis psicossocial. Esta pesquisa apresenta o Núcleo de Apoio à Saúde da Família (NASF) como uma ressonância do entrelaçar dos movimentos reformistas do campo da saúde no Brasil (Reforma Sanitária e Reforma Psiquiátrica). O NASF é um programa do Ministério da Saúde, criado em 2008, com o objetivo de fortalecer e ampliar o escopo de ações da Estratégia Saúde da Família, contribuindo, assim, para catalisar a reorientação do modelo de atenção à saúde no país. Nosso interesse foi o de investigá-lo enquanto um dispositivo capaz de mobilizar a práxis psicossocial e contribuir para o desenvolvimento de atenção à saúde mental, no âmbito da Atenção Básica. Para tanto, buscamos conhecer as propostas e ações desenvolvidas por profissionais de um NASF, em um município do interior do Paraná. A pesquisa situa-se no campo das metodologias qualitativas e tem sua orientação metodológica pautada na concepção de homem como um ser histórico, capaz de transformar a realidade e ser transformado por ela, numa constante interação com o meio social e com o mundo material. A partir dessa orientação metodológica, utilizamos o conceito de ...
Keywords: Reforma psiquiátrica; Saude mental; Cuidados primários de saúde; Mental health; Brasil